2010
DOI: 10.1097/pas.0b013e3181d95c37
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Histologic Risk Model in a New Cohort of Patients With Head and Neck Squamous Cell Carcinoma

Abstract: We demonstrate significant predictive performance of the risk model in a new cohort of patients with primary HNSCC, adjusted for confounders. Our training experience also supports the feasibility of adapting the risk model in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
190
2
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 196 publications
(209 citation statements)
references
References 19 publications
9
190
2
8
Order By: Relevance
“…Earlier models by Bryne et al [5,6], Bundgaard et al [18] involved multiparameter histopathological grading system based on pattern of tumor invasion (POI), degree of keratinisation, nuclear pleomorphism and lymphocytic host response for prognosis of oral cancer. Similarly later a novel histologic risk scoring scheme was developed and validated by BrandweinGensler [7,8] which included perineural invasion in addition to Bryne's parameters for decision making and adjuvant treatment in head and neck cancer. Although several such histopathological parameters, grading systems and risk models have been described in literature, none is universally accepted because their clinical utility and reproducibility have not been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier models by Bryne et al [5,6], Bundgaard et al [18] involved multiparameter histopathological grading system based on pattern of tumor invasion (POI), degree of keratinisation, nuclear pleomorphism and lymphocytic host response for prognosis of oral cancer. Similarly later a novel histologic risk scoring scheme was developed and validated by BrandweinGensler [7,8] which included perineural invasion in addition to Bryne's parameters for decision making and adjuvant treatment in head and neck cancer. Although several such histopathological parameters, grading systems and risk models have been described in literature, none is universally accepted because their clinical utility and reproducibility have not been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Bryne et al had developed a multiparameter histopathological grading system based on pattern of tumor invasion (POI), degree of keratinisation, nuclear pleomorphism and host response for prognosis of oral cancer [5,6]. Similar histologic risk scoring scheme for decision making and adjuvant treatment in head and neck cancer has been developed and validated by Brandwein-Gensler [7,8]. Although several such histopathological parameters and grading systems have been developed and refined in literature, none is universally accepted.…”
Section: Introductionmentioning
confidence: 99%
“…It is also significantly associated with poorer outcome as compared to small nerve involvement or no perineural invasion. We have recently completed the first validation study on a cohort of 305 patients with primary HNSCC of the oral cavity, oropharynx, and larynx, from three different institutions [26]. The median follow-up period for all patients was 27 months.…”
Section: Predictors Of Occult Metastases: Tumor Depth Of Invasionmentioning
confidence: 99%
“…Weak LHR was assigned for limited response that lacks any lymphoid nodules. We have demonstrated that strong LHR at the interface is associated with improved outcome [1], which is consistent with the concept that enhanced immune surveillance and adaptive immunity have protective impact for cancer patients [3]. Similarly, light microscopic assessment of tumor-infiltrating lymphocytes (categorized as either brisk, non-brisk, or absent) has been demonstrated to be a valuable prognosticator for patients with stage I/II cutaneous melanoma and vertical growth, as it significantly directly correlates with survival [4].…”
Section: Introductionmentioning
confidence: 98%
“…The histological Risk Model significantly correlates with disease progression and survival for patients with primary head and neck squamous cell carcinoma (HNSCC) when adjusted for clinical confounders [1,2]. The model is based on the histological examination of resection specimens for oral and oropharyngeal squamous carcinomas, with the classification of three histological variables: worst pattern of invasion, perineural invasion and lymphocytic host response (LHR).…”
Section: Introductionmentioning
confidence: 99%